THE ROLE OF DENTAL ASSISTANTS IN MANAGING MEDICAL EMERGENCIES IN THE DENTAL OFFICE. A NARRATIVE REVIEW. - Munirah Mohammed Almutairi, Jehad jaber al harash, Rahmah Abdullah Alsultan, Marwa Mohammed Amin Habhab, Ghadeer Abdulhadi Alkhalawi, Zahrah Essa Ali Alnaji, (Chelonian Research Foundation, 2024)
Medical emergencies in the dental office, although rare, present significant risks to patient safety and require immediate attention to prevent adverse outcomes. Dental assistants (DAs) are critical members of the dental healthcare team who play a pivotal role in managing these emergencies. This review explores the responsibilities and contributions of dental assistants in responding to medical emergencies, highlighting their training, responsibilities, and the importance of effective teamwork. By synthesizing existing literature, the review underscores the essential skills and knowledge that dental assistants should possess, as well as the protocols and procedures they should follow to enhance patient care during medical emergencies. It is concluded that proper training and clear roles for dental assistants are vital for the effective management of such events.